2011
DOI: 10.2298/tsci110608067h
|View full text |Cite
|
Sign up to set email alerts
|

Practical data correlation of flashpoints of binary mixtures by a reciprocal function: The concept and numerical examples

Abstract: Simple data correlation of flashpoint data of binary mixture has been developed on a basic of rational reciprocal function. The new approximation requires has only two coefficients and needs the flashpoint temperature of the pure flammable component to be known. The approximation has been tested by literature data concerning aqueous-alcohol solution and compared to calculations performed by several thermodynamic models predicting flashpoint temperatures. The suggested approximation provides accuracy comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The method was conceived with data about FP of water-alcohol mixtures [14] using the relationship based on following reciprocal function: where y is the scaled (dimensionless) FP temperature of given flammable mixture and x -the molar fraction of the alcohol. In eq.…”
Section: One Flammable Componentmentioning
confidence: 99%
See 2 more Smart Citations
“…The method was conceived with data about FP of water-alcohol mixtures [14] using the relationship based on following reciprocal function: where y is the scaled (dimensionless) FP temperature of given flammable mixture and x -the molar fraction of the alcohol. In eq.…”
Section: One Flammable Componentmentioning
confidence: 99%
“…Additionally, some examples of mixtures exhibiting strong concave behavior due to partial immiscibility of components were tested. Mixtures with extrema (maxima or minima) in the FP [13][14][15][16] are beyond the scope of Table 2. Mixture flash points of n-decane(1)-n-dodecane(2)…”
Section: The Target Of the Proposed Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The results exhibited differences between experimental and predicted values for some nonideal binary blends such as ethanol/ n -octane (4.5 °C) and methanol/methyl acetate (6 °C). Some methods have correlated FP with the physical properties of the blend components, but they are not extensible to blends composed of other substances. Agarwal et al, Liu et al, and Kumar et al used neural networks to predict FP of aviation fuels and biodiesel fuels (blends of different methyl esters) and reported better results than those obtained previously from correlations.…”
Section: Introductionmentioning
confidence: 99%
“…However, they pointed out that QSPR methods, combined with near-infrared spectroscopy, will have even better prediction capability in the future. In addition, Phoon et al compared the methods based on correlations , with those based on QSPR and with those based on the Le Chatelier equation ,, and found that the best prediction capability was obtained with the latter ones, even in the case of nonideal mixtures. Among these methods, that proposed by Liaw was proved to be the most efficient.…”
Section: Introductionmentioning
confidence: 99%